Pedigree reconstruction reveals large scale movement patterns and population dynamics of wolverines (Gulo gulo) across Fennoscandia - Higgins, Stephanie (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
Dispersal is a biological imperative for many species, facilitating gene flow and influencing population dynamics. Modern landscapes are increasingly fragmented, leaving species that rely on dispersal trapped in ever shrinking areas. Measuring connectivity at the population level is difficult using traditional tracking methods, especially for species that are rare or cryptic, but important for both theoretical and applied questions relating to animal movement.